Progress in Photocatalyzed Trifluoromethylthiolation and Trifluoromethylselenolation Reactions - Li, Fei; Song, Jia-Wei; Han, Xue; Zhang, Cheng-Pan (Synthesis, 2024)
The trifluoromethylthio (SCF3) and trifluoromethylselanyl (SeCF3) groups possess high electron-withdrawing ability, excellent lipophilicity, good stability, and bioavailability, and they are promising structural motifs in drug design and development. Photoredox catalysis has clear benefits; it is a mild and sustainable methodology for the modification of chemical structures that enables a variety of chemical reactions that are unattainable using classical ionic chemistry. This review focuses on light-initiated trifluoromethylthiolation and trifluoromethylselenolation reactions with diverse SCF3 and SeCF3 reagents. Representative transformations either using photocatalysts or through EDA complexes, as well as possible reaction mechanisms, are all discussed in this article.1 Introduction2 Photocatalyzed Trifluoromethylthiolation2.1 Photocatalyzed Trifluoromethylthiolation with MSCF3 (M = H, [Me4N], Ag)2.2 Photocatalyzed Trifluoromethylthiolation with XSCF3 (X = Cl, CF3S)2.3 Photocatalyzed Trifluoromethylthiolation with ArSO2SCF32.4 Photocatalyzed Trifluoromethylthiolation with N–SCF3 Reagents2.5 Photocatalyzed Trifluoromethylthiolation with Other Reagents3 Photocatalyzed Trifluoromethylselenolation3.1 Photocatalyzed Trifluoromethylselenolation with [Me4N][SeCF3]3.2 Photocatalyzed Trifluoromethylselenolation with ArSO2SeCF34 Summary
Keywords: trifluoromethylthiolation; trifluoromethylselenolation; visible-light irradiation; photoredox catalysis; radical; photocatalysis